2009
DOI: 10.1094/mpmi-22-4-0421
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Distinct Defense-Associated Protein Patterns in Aphanomyces euteiches (Oomycota)–Elicited and –Inoculated Medicago truncatula Cell-Suspension Cultures: A Proteome and Phosphoproteome Approach

Abstract: A comprehensive proteomic approach was applied to investigate molecular events occurring upon inoculation of Medicago truncatula cell-suspension cultures with the oomycete root pathogen Aphanomyces euteiches. Establishment of an inoculation assay in the cell cultures allowed a direct comparison between proteins induced by elicitation with a crude culture extract of the oomycete and by inoculation with A. euteiches zoospores representing the natural infection carrier. Oxidative burst assays revealed responsiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…Therefore, we examined whether the suppression of MtROP9 alters ROS levels in MtROP9i roots. ROS accumulation was measured in root segments of MtROP9i, Mtvector, and Mtwt after inoculation by a luminol-based chemiluminescence assay to determine the production of H 2 O 2 during a period of 1 h after the application of two spore inocula: (1) 500 mL of lake water containing 250,000 Aphanomyces euteiches vital zoospores, as described previously (Trapphoff et al, 2009); and (2) 500 mL of water inoculum containing 10,000 viable Glomus intraradices spores. These measurements revealed clearly reduced ROS production in the MtROP9i transgenic roots as compared with the Mtwt and Mtvector root segments (Fig.…”
Section: Mtrop9i Transgenic Roots Show Clear Reductions Of Ros Accumumentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we examined whether the suppression of MtROP9 alters ROS levels in MtROP9i roots. ROS accumulation was measured in root segments of MtROP9i, Mtvector, and Mtwt after inoculation by a luminol-based chemiluminescence assay to determine the production of H 2 O 2 during a period of 1 h after the application of two spore inocula: (1) 500 mL of lake water containing 250,000 Aphanomyces euteiches vital zoospores, as described previously (Trapphoff et al, 2009); and (2) 500 mL of water inoculum containing 10,000 viable Glomus intraradices spores. These measurements revealed clearly reduced ROS production in the MtROP9i transgenic roots as compared with the Mtwt and Mtvector root segments (Fig.…”
Section: Mtrop9i Transgenic Roots Show Clear Reductions Of Ros Accumumentioning
confidence: 99%
“…Oxidative burst measurements were performed using a luminol-based chemiluminescence assay to determine the production of H 2 O 2 during a period of 1 h after application of microbial fractions to root fragments of MtROP9i, Mtvector, and Mtwt as described previously (Trapphoff et al, 2009). For the measurements, 20 root pieces of 0.5 cm length were collected from MtROP9i, Mtvector, and Mtwt each and transferred to 200 mL of tap water in illuminometer cuvettes.…”
Section: Measurement Of Ros Oxidative Burstmentioning
confidence: 99%
See 1 more Smart Citation
“…Several characterized protein kinases are required for symbiosis signal transduction in M. truncatula roots (Lévy et al, 2004;Yoshida and Parniske, 2005;Smit et al, 2007). A recent antibodybased study of cultured M. truncatula cells observed protein phosphorylation changes at the proteomic level in response to fungal infection (Trapphoff et al, 2009); however, the target residues of the phosphorylation events were not determined. A variety of studies have determined in vitro phosphorylation sites on legume proteins and demonstrated the biological importance of the target residues by mutagenesis (Yoshida and Parniske, 2005;Arrighi et al, 2006;Lima et al, 2006;Miyahara et al, 2008;Yano et al, 2008).…”
mentioning
confidence: 99%
“…(3) Is there a Cyclamenspecific auxin accumulation profile? To resolve the new questions concerning post-translational modifications a gelor mass spectrometry-based approach like performed by Trapphoff et al (2009) or Grimsrud et al (2010 could be helpful. A metabolic profiling of auxin levels in the different stages of embryogenesis of Cyclamen could elucidate the dynamics of this plant hormone and its correlation to auxin-amidohydrolase and auxin-storage conjugates.…”
Section: Discussionmentioning
confidence: 99%